Synthesis, characterization and adsorption studies of a novel triptycene based hydroxyl azo- nanoporous polymer for environmental remediation. Issue 2 (April 2020) - Ansari, Mosim; Alam, Akhtar; Bera, Ranajit; Hassan, Atikur; Goswami, Santu; Das, Neeladri
Graphical abstract: Highlights: A facile and green synthesis of a new triptycene based nanoporous polymer (TBHAP ). TBHAP has high SABET (824 m 2  g −1 ) and CO2 uptake (145.8 mg g −1 at 273 K, 1 bar). CO2 /N2 selectivity of TBHAP is reasonably high (84 measured at 273 K). TBHAP rapidly captures cationic dye from a binary mixture of cationic/anionic dyes. TBHAP efficiently and reversibly captures iodine (up to 1880 mg g −1 ). Abstract: Gradual increase in CO2 emission due to energy production from fossils fuels is a major contributor to global warming. Alternatively, "carbon free" nuclear energy generates radioactive and carcinogenic iodine vapors. Thus, the need to develop efficient sorbents for capture of CO2 and I2 is justified. Herein, we report a Triptycene-based-Hydroxyl-Azo-Polymer (TBHAP ) derived from relatively inexpensive hydroquinone (one of the two monomers) and using water as a solvent. TBHAP is thermally stable and nanoporous with high surface area (SABET up to 824 m 2 g −1 ). The presence of permanent porosity (due to triptycene), π-rich cavities (from abundant arene rings) and active functional groups [phenolic−OH and azo (NN)] in the polymeric network of TBHAP makes it effective for reversible iodine (188 wt%), H2 (8.9 mg g −1 : 77 K, 1 bar) and CO2 (145 mg/g: 273 K, 1 bar) uptake with moderately high CO2 /N2 selectivity (84 at 273 K). TBHAP is also an effective and selective adsorbent for toxic cationic dyes [Methylene blue (Qm = 250 mg g −1 ) and Rhodamine B (Qm = 588 mg g −1 )] from an aqueous solution containing binary mixtures of cationic/anionic dyes. Thus, TBHAP is a versatile porous material with various applications in the domain of environmental remediation.